2021
DOI: 10.1111/oik.07810
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional soil heterogeneity modulates responses of grassland mesocosms to an experimentally imposed drought extreme

Abstract: Heterogeneity is an intrinsic characteristic of soils, which regulates plant diversity and ecosystem functioning. However, whether soil heterogeneity also modulates responses of plant communities to climate change, including climate extremes, remains largely an open question. Here, we explore responses of plant communities to drought extremes across four levels of spatial soil heterogeneity, with cell sizes varying from very small to very large, i.e. 0, 12, 24 and 48 cm. These were created in mesocosms by alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…patchy soil types and fluctuating soil nutrients) could provide different resources in different patches, thereby creating more niche opportunities for various species, and thus promote species coexistence and species richness (Beck & Givnish, 2021; Levine & HilleRisLambers, 2009). Second, heterogeneous soils are usually more likely to provide shelter and refuges under stressful conditions, which also promotes species coexistence and species richness (Hutchings et al, 2003; Liu et al, 2021; Stover & Henry, 2019). Such heterogeneity–species richness relationships are more pronounced at large spatial scales, while at small spatial scales the pattern still remains unclear (Stein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…patchy soil types and fluctuating soil nutrients) could provide different resources in different patches, thereby creating more niche opportunities for various species, and thus promote species coexistence and species richness (Beck & Givnish, 2021; Levine & HilleRisLambers, 2009). Second, heterogeneous soils are usually more likely to provide shelter and refuges under stressful conditions, which also promotes species coexistence and species richness (Hutchings et al, 2003; Liu et al, 2021; Stover & Henry, 2019). Such heterogeneity–species richness relationships are more pronounced at large spatial scales, while at small spatial scales the pattern still remains unclear (Stein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in grasslands, clumped sowing might improve diversity and coexistence which could improve ecosystem resistance/resilience to climate extremes (Oliveira et al, 2022 ), without reducing productivity. However, Liu et al ( 2021 ) found small‐scale soil heterogeneity can increase drought stress because of the enhanced biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…However,Liu et al (2021) found small-scale soil heterogeneity can increase drought stress because of the enhanced biomass production.Heterogeneous fertilization could perhaps allow for a reduction in fertilizer use. Whether management can effectively be improved by putting heterogeneity to use remains an open question, but understanding the role of soil heterogeneity is clearly crucial to answering it.…”
mentioning
confidence: 99%
“…Several studies have revealed that soil nutrient heterogeneity can interact with global change factors such as elevated CO 2 concentration, nitrogen enrichment and changes in rainfall regime to influence plant communities (Maestre et al 2005, Maestre and Reynolds 2006, 2007a, Godfree et al 2011, Liu et al 2021). These interactions occur because the component plant species often differ in the direction and magnitude of their responses to soil nutrient heterogeneity (Hutchings et al 2003) and global change factors (García‐Palacios et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, soil nutrient heterogeneity reduced the positive effects of elevated CO 2 on plant community productivity (Maestre et al 2005), but increased the positive effects of enhanced nutrient availability on plant community productivity (Maestre and Reynolds 2006), via changing root foraging precision of the community. More recently, the impacts of drought on plant communities were found to be more pronounced at intermediate levels of soil nutrient heterogeneity due to drought‐induced changes in soil properties (Liu et al 2021). These results indicate that soil nutrient heterogeneity may modify the impacts of global change factors on plant communities, depending on which global change factor is acting on them.…”
Section: Introductionmentioning
confidence: 99%